Remaking New Orleans : Beyond Exceptionalism and Authenticity - Sakakeeny, Matt, 1971-; Adams, Thomas Jessen (Book collections on Project MUSE., 2019)
The contributors to Remaking New Orleans challenge the uncritical acceptance of New Orleans-as-exceptional narratives, showing how they flatten the diversity, experience, and culture of the city's residents and obscure other possible understandings.